Study on epidemiology, risk factors and clinical characteristics of triple negative breast cancer in Bangladesh - Zohora, Fatema Tuz; Rabbi, Mohammad Fazle (International Journal of Research in Medical Sciences, 2018)
Breast cancer is the second most common type of cancer in Bangladesh. Although significant improvement has been made in breast cancer treatment and management, Triple Negative Breast Cancer (TNBC) is still the least known breast cancer subtype in this country. TNBC is well known for its aggressive nature and limited therapeutic options when compared to other breast cancer subtypes. Several population-based studies indicated high prevalence of TNBC in African women in addition to few recent studies indicating a growing number of TNBC patients among Asian population. However, there is a lack of evidence on TNBC patients in Bangladesh due to limited knowledge and awareness. In this paper we review the epidemiology, general risk factors and clinical characteristics of TNBC to find out the correlation between TNBC and other conventional breast cancer subtypes in Bangladesh. Some diagnostic and therapeutic approaches as well as future novel solutions for TNBC are also discussed to understand the pathologic process and treatment strategies of TNBC. Literature review reveals that, there is a lack of TNBC studies in Bangladesh. Therefore, more investigations should be carried out to address the degree of vulnerability of TNBC in breast cancer patients of Bangladesh.